Experimental methods for engineers - Holman, J.P (Mcgraw-Hill series in mechanical engineering, 2012)
Experimental Methods for Engineers, 8/e, offers the broadest range of experimental measurement techniques available for mechanical and general engineering applications. Offering clear descriptions of the general behavior of different measurement techniques, such as pressure, flow, and temperature, the text emphasizes the use of uncertainty analysis and statistical data analysis in estimating the accuracy of measurements. Maintaining its thorough coverage of thermal-fluid measurement techniques, the text continues to emphasize experimental uncertainties as essential elements in experiment design, execution, and instrument selection.